STRATEGI PENGEMBANGAN KEMAMPUAN SOSIAL EMOSIONAL BERBASIS KEARIFAN LOKAL DI TK MUSLIMAT NU 089 KEPATIHAN PONOROGO - Rohmad Arkam; Mulyono (Universitas Islam Balitar, 2020)
The purpose of this study was to determine strategies for developing social emotional skills based on local wisdom in TK Muslimat NU 089 Kepatihan Ponorogo. This research is a descriptive study, a case study in TK Muslimat NU 089 Kepatihan Ponorogo. In collecting data, the authors use the interview, observation, and documentation methods, while the data analysis techniques used are data reduction, data display and conclusion drawing or verification. The results of the research that has been done are found, that; strategy of developing emotional social skills based on local wisdom in TK Muslimat NU 089 Kepatihan Ponorogo is to use organizational and collaborative strategies, organizational strategy can be seen by picking up some local wisdom around the institution and then taking one of the local wisdoms in the form of dolanan song then made into dolphin song the basis of development while the usual collaboration strategy is evidenced by the collaboration between TK Muslimat NU 089 Kepatihan Ponorogo and the Education Office of the Regency of Ponorogo by holding mass dance and dolanan song.